Assessment of undiscovered nickel sulphide resources, Kalgoorlie Terrane, Western Australia: Part 1. deposit and endowment density models - Mamuse, Antony; Beresfordb, Steve; Porwala, Alok; Kreuzer, Oliver (Elsevier, 2016)
The use of mineral deposit density regression models to estimate the number of undiscovered deposits is gaining acceptance in mineral resources assessments. The deposit density regression models currently in use are based on well-established power law relationships between deposit density (deposits/km2) and the areal extent of the host rocks in well explored regions (control areas) worldwide. Although these generalized or global deposit density models can generate guideline estimates that are useful at the terrane scale, locally-derived terrane-based deposit density regression models may potentially yield more relevant estimates at the terrane scale. Using 12 selected komatiite-defined control areas in the Kalgoorlie Terrane, Western Australia, we found that the size (km2) of the control areas had power law relationships with (i) nickel sulphide deposit density, and (ii) nickel endowment density (nickel metal/km2). Regression analyses showed that both power law relationships are statistically significant at the 5% level. This suggests that nickel sulphide deposit and endowment density models could be used to estimate the number of undiscovered nickel sulphide deposits and amount of nickel metal endowment in less explored komatiites in the Kalgoorlie Terrane. This study shows that global geological relationships can be viably downscaled onto local geological terranes thereby supporting the hypothesis that the processes of mineral deposit formation and preservation are scale-independent and self-similar.